Powder Fruit Bit (Beta Bulgaris) To Decrease Of Blood Pressure In Hypertension Patients - Apidianti, Sari Pratiwi; Yunita, Emi (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The study design used a pre-experimental, one group pre-post test design. The population is all people with hypertension in the Coastal Area, Pademawu District, Pamekasan Regency, East Java Province. Subjects were 40 respondents using total sampling. The independent variable was beet powder (Beta Bulgaris) and the dependent variable was blood pressure. Data were collected using a digital tensimeter and analyzed with Wilcoxon (α <0.05). The results of the study had an average systolic blood pressure of 165 mmHg and a diastolic of 93 mmHg. The difference in systolic blood pressure results ρ = 0.000 (Negative Rank: 28, Positive Rank: 6, Ties: 6) diastolic results ρ = 0.293. The results of the analysis ρ <α, then there is a significant difference in systolic blood pressure before and a container of Beetroot Powder (Beta Bulgaris) Against Decreasing BloodHypertensive Patients Blood